Roles of Malaysian online newspapers in the construction of public opinion on rare earth risks - Hasan, Nik Norma Nik; Dauda, Sharafa (Center for Asian Public Opinion Research & Collaboration Initiative (CAPORCI), 2020)
This study explored the representation of risks from the controversial Lynas rare earth refining as a risk event by five Malaysian online mainstream and alternative newspapers using qualitative content analysis. The aim is to uncover the role of the news media in the social amplification and attenuation of risks within the literature evidence as those roles are still uncertain. Content analysis is used to explore the online newspapers’ roles guided by the Social Amplification of Risk Framework (SARF). The representations typified environmental, financial, health, occupational, property, radioactive, and technological risks and established connections between four risk types (environmental, financial, radioactive, and health risks).